What is the Role of Mannose-Binding Lectin Gene Polymorphism in the Development of Acute Post-Streptococcal Glomerulonephritis? - Deniz Güven; Mustafa Bak; Erkin Serdaroğlu; Ferda Özkınay; Ayça Aykut (Galenos Publishing House, 2021)
Objective: This study aims to determine the effects of the mannose-binding lectin (MBL) gene polymorphism on the clinical and laboratory findings, response to treatment, and progress of patients with acute post-streptococcal glomerulonephritis (APSGN). Methods: Codon 54 polymorphism found in exon 1 of the MBL gene was investigated by polymerase chain reaction-restriction fragment length polymorphism method in 110 children followed up with the diagnosis of APSGN and compared with healthy control group. Results: The normal allele AA and, the variant alleles AB and BB gene frequencies were determined within the APSGN group as 74.5%, 20% and, 5.5%, respectively. No statistically significant difference was found with concerning to the gene polymorphism in the APSGN group when compared with the control group (p>0.05). No correlation was found in the patient group between gene polymorphism and the presence of hematuria, edema, central nervous system findings, and blood pressure (p>0.05). Concerning laboratory findings during the diagnosis, no correlation existed between the gene polymorphism and high levels of urea, creatine, total cholesterol, and triglycerides, low levels of albumin, and the presence of proteinuria (p>0.05). Within the first years following the diagnosis, no statistically significant difference was found in the glomerular filtration rates, blood creatine levels, proteinuria levels, duration of microscopic hematuria and proteinuria between the patients with the gene polymorphism and those without the gene polymorphism (p>0.05) Conclusion: Our study determined that the MBL gene polymorphism was not important in the development, the laboratory and clinical findings, or the progression of the patients with APSGN.